Biological properties and chemical diversity of Sinularia Flexibilis, an Alcyonacean Soft Coral - Nagappan, Thilahgavani; Palaniveloo, Kishneth (Universiti Malaysia Terengganu, 2018)
Soft corals of the genus Sinularia (order Alcyonacea) are one of the most widespread sessile organisms in the Indo-Pacific waters. Unlike the hard corals, the major portion of soft coral is made up of inorganic skeletons consisting of calcareous spicules surrounded by a thin layer of tissue. This layer of tissue, made up of fleshy colonies with organic matter, is responsible in diversity of secondary metabolites. In order to survive the outburst of algal bloom, dynamic of microbial growth and predation of marine organisms, these soft corals synthesize unique chemicals as part of defense mechanism that makes them unpalatable to most marine life. As such, members of the genus Sinularia exhibits a diversity of secondary metabolites ranging from sesquiterpenes, diterpenes, polyhydroxylated steroids, and polyamine compounds. These metabolites had been shown to possess various biological activities such as antimicrobial, anti-inflammatory and cytotoxicity. This present paper reviews the chemistry and highlights the potential biological activities of metabolites from Sinularia flexibilis and provides a perspective for future research.